Acute Coronary Syndrome (ACS) due to Coronary Artery Embolism in a Patient with Atrial Fibrillation. (10th October 2019) - Daoud, Hussein; Abugroun, Ashraf; Erramilli, Shruti; Kumar, Surender
Abstract : Acute coronary syndrome (ACS) secondary to a coronary embolism is an unusual occurrence, yet an important consideration given the difficult diagnosis. We report a case of a 69-year-old male with a medical history of paroxysmal atrial fibrillation who presented with chest pain and shortness of breath. A coronary angiogram was significant for three focal transluminal and translucent areas in the ostial, mid, and distal circumflex artery consistent with embolic disease. The patient was subsequently managed medically with anticoagulation. Despite being a relatively rare entity, thromboembolism into the coronary arteries can provoke an acute myocardial infarction, with atrial fibrillation being the most common risk factor. Treatment modalities for ACS secondary to thromboembolism include stent placement, intracoronary thrombolysis, and thrombus aspiration.